Exploration Concept of Physics on Local Wisdom in Traditional Game Angkle (Engklek) as Student Teaching Material - Eka Putri Dian Nata Sari; Mohd Zaidi Bin Amiruddin; Setyo Admoko; Nadi Suprapto; Suliyanah Suliyanah (Berkala Ilmiah Pendidikan Fisika, 2023)
Local wisdom is a characteristic or culture that develops within the local scope from generation to generation in a certain area or region with cultural values. This engklek is a game that is done by doing the engklek, angkle, or angkling movement, namely walking and jumping using one leg. This study aims to explore and analyze the relationship between physics concepts and hopscotch games. This research method uses a qualitative research method in the form of a literature study. Data collection techniques in this study were observation and documentation. The data sources used in this study are observation as primary data and literature review as secondary data. The data that has been obtained will be reduced according to the needs to be achieved. Sources of data in this study are divided into 2, namely primary data and secondary data. Primary data is done by observing and documenting the crank game. Secondary data were obtained by reviewing 7 articles between 2016 - 2021. The results of this study found that there are physics concepts in the engklek game, namely parabolic motion, Newton's law, and rigid body equilibrium. This can make the engklek game an alternative learning media with concrete examples in the surrounding environment. The concept of physics can be found in the surrounding or nearby environment to be used as a more meaningful learning resource. The meaningful learning question is that learning can make it easier for students to understand learning because it connects concepts with real life.